Elaboration of criteria for development of sustainable motorways of the sea services - Žgaljić, Dražen (Array, 2019)
The maritime transport system in the Adriatic region has been developed thanks to the individual activities of ports, as well as specific strategies for the development of the countries that gravitate towards that region. Regarding its potential, this system is not sufficiently developed and there are no clear criteria for evaluating the potential for success of the future Motorways of the Sea systems and services. The solution to this problem is in the scientific point of view that should contribute to the development of the Motorways of the Sea with its systematic approach and clearly defined criteria of implementation of specific models and common activities. With this scientific article and conducted research, we tried to cover the greater part of the whole transport chain (from the departure point to the destination) which is present in the Adriatic region. It is crucial that we take into consideration the fact that it wasn’t possible to gather and analyze the data for every land direction (highways and railways) because we analyzed the infrastructure of the whole region. Thus, the research in this article is directed to the ports and their entries, where the success factor of the port is determined by the success of the direction and the Motorways of the Sea service. In order to accurately determine each of the defined success factors, it was necessary to identify all the subelements which comprise them. The research results point out the complexity of developing new or improving the existing MoS services at higher levels (administrative, infrastructural, organizational, etc.).